58.1k views
2 votes
What are the roots of the equation x2 - 5x + 6 = 0?

A
1 and -6
B.
2 and 3
C
-1 and 6
D.
-2 and -3​

User Alukach
by
5.9k points

1 Answer

5 votes

The answer is

B. -2 and 3

Step-by-step explanation :

Given the expression

x²- 5x + 6 = 0

Firstly we need to find two numbers that when multiplied will give us the constant term 6, and when added will give us the 2nd term 5

These numbers are 3 and 2

Substituting 2x +3x for 5x

x²- (2x+3x)+ 6 = 0

x²-2x-3x+6=0

(x²-2x)-(3x+6)=0

Factoring we have

x(x-2)-3(x-2)=0

x-3=0, x-2=0

x=3, x= 2

User Guillaume Laurent
by
6.4k points